Random Nanowires of Nickel Doped TiO2 With High Surface Area and Electron Mobility for High Efficiency Dye-Sensitized Solar Cells - Rajan, Jose; M. M., Yusoff; Archana, P. S.; Kumar, E. Naveen; Vijila, C.; Ramakrishna, S. (Royal Society of Chemistry, 2013)
Mesoporous TiO(2) with a large specific surface area (~150 m(2) g(-1)) is the most successful material in dye-sensitized solar cells so far; however, its inferior charge mobility is a major efficiency limiter. This paper demonstrates that random nanowires of Ni-doped TiO(2) (Ni:TiO(2)) have a dramatic influence on the particulate and charge transport properties. Nanowires (dia ~60 nm) of Ni:TiO(2) with a specific surface area of ~80 m(2) g(-1) were developed by an electrospinning technique. The band gap of the Ni:TiO(2) shifted to the visible region upon doping of 5 at% Ni atoms. The Mott-Schottky analysis shows that the flat band potential of Ni:TiO(2) shifts to a more negative value than the undoped samples. The electrochemical impedance spectroscopic measurements showed that the Ni:TiO(2) offer lower charge transport resistance, higher charge recombination resistance, and enhanced electron lifetime compared to the undoped samples. The dye-sensitized solar cells fabricated using the Ni:TiO(2) nanowires showed an enhanced photoconversion efficiency and short-circuit current density compared to the undoped analogue. The transient photocurrent measurements showed that the Ni:TiO(2) has improved charge mobility compared with TiO(2) and is several orders of magnitude higher compared to the P25 particles.